2022
DOI: 10.3390/brainsci12121595
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Experience of the Effects of Cladribine Tablets on Lymphocyte Subsets and Serum Neurofilament Light Chain Levels in Relapsing Multiple Sclerosis Patients

Abstract: Although cladribine induces sustained reductions in peripheral T and B lymphocytes, little is known about its effect on axonal damage reduction in multiple sclerosis (MS), which could be demonstrated by assessing the serum neurofilament light chain (sNfL) levels. We investigated the reduction/reconstitution of different lymphocyte subsets (LS) by verifying the correlation with no evidence of disease activity (NEDA) and the variation in sNfL levels during cladribine treatment. We analysed 33 highly active relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…SNfL reductions among our cohort were clinically accompanied by amelioration of median EDSS. Our results are in line with a recent Italian study, which observed a similar strong reduction of sNfL at 24 weeks among 18 MS patients [ 9 ]. While the exact mode of action of CLAD remains elusive, the impact on central nervous system inflammation appears mainly attributed to the peripheral consequences of the drug on circulating lymphocytes [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…SNfL reductions among our cohort were clinically accompanied by amelioration of median EDSS. Our results are in line with a recent Italian study, which observed a similar strong reduction of sNfL at 24 weeks among 18 MS patients [ 9 ]. While the exact mode of action of CLAD remains elusive, the impact on central nervous system inflammation appears mainly attributed to the peripheral consequences of the drug on circulating lymphocytes [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Whereas the evidence on the effect of CladT on T cells is more variable with some studies noting a significant decrease in T cell number with delayed repletion 15,28 , whilst others reported a less pronounced effect on the overall T cell population with involvement of CD4+ T cells or central memory T cells 26,29,30 , or no or limited effect on CD8+ T cells 27,29 . We noted in our cohort better depletion in CD4+/CD8+ central memory, effector memory and TEMRA T cells after the second cycle of CladT 26 , but with an early compensatory rise regulatory T cells (FoxP3+) after the first course of CladT reaching a high at week 3 similar to some other findings 31 .…”
Section: Discussionsupporting
confidence: 90%
“…A real-life study of 14 cladribine-treated PwMS also found no relationship between sNfL levels and relapse, neuroimaging activity, EDSS progression, or NEDA-3 status [31]. Likewise, no correlation was reported between sNfL levels and NEDA-3 in 74 PwMS treated with CLD [54] or in 52 PwMS treated with DMF after 12 months of follow up [27]. However, studies with longer follow-up periods have demonstrated an association between baseline sNfL levels and the presence of clinical and radiological activity or EDSS progression [9,30,33,35,49,55].…”
Section: Discussionmentioning
confidence: 97%